Resilience—Towards an interdisciplinary definition using information theory - Nisioti, Eleni; Clark, Colby; Das, Kaushik Kunal; Ernst, Ekkehard; Friedenberg, Nicholas A.; Gates, Emily; Lambros, Maryl; Lazurko, Anita; Puzović, Nataša; Salas, Ilvanna (Frontiers in Complex Systems, 2023)
The term 'resilience' has risen in popularity following a series of natural disasters, the impacts of climate change, and the pandemic. However, different disciplines use the term in widely different ways, resulting in confusion regarding how the term is used and difficulties operationalising the underlying concept. Drawing on an overview of eleven disciplines, our paper offers a guiding framework to navigate this ambiguity by suggesting a novel typology of resilience using an information-theoretic approach. Specifically, we define resilience by borrowing an existing definition of individuals as sub-systems within multi-scale systems that exhibit temporal integrity amidst interactions with the environment. We quantify resilience as the ability of individuals to maintain fitness in the face of endogenous and exogenous disturbances. In particular, we distinguish between four different types of resilience: (i) preservation of structure and function, which we call "strong robustness"; (ii) preservation of function but change in structure ("weak robustness"); (iii) change in both structure and function ("strong adaptability"); and (iv) change in function but preservation in structure ("weak adaptability"). Our typology offers an approach for navigating these different types and demonstrates how resilience can thus be operationalised across disciplines.